2021
DOI: 10.1111/nicc.12732
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of the use of virtual reality in intensive care units

Abstract: BackgroundA wide range of reviews have demonstrated the effectiveness and tolerability of Virtual Reality (VR) in a range of clinical areas and subpopulations. However, no previous review has explored the current maturity, acceptability, tolerability, and effectiveness of VR with intensive care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…The present study is the first randomized study about VR evaluating the improvement in overall patient baseline comfort in a mixed medical-surgical ICU, compared to music therapy and standard relaxation. A recent review on VR in ICU reported 21 studies, mostly of them being observational, non-comparative, feasibility studies [43], whose reports are consistent with the present study with a completion rate of 74%, (95%CI 51%-96.0%). In two proof-of-concept studies designed by the same group, heart rate and blood pressure decreased in 37 patients [44], while respiratory rate and discomfort decreased in 33 patients [45].…”
Section: Table 2 (Continued)supporting
confidence: 90%
“…The present study is the first randomized study about VR evaluating the improvement in overall patient baseline comfort in a mixed medical-surgical ICU, compared to music therapy and standard relaxation. A recent review on VR in ICU reported 21 studies, mostly of them being observational, non-comparative, feasibility studies [43], whose reports are consistent with the present study with a completion rate of 74%, (95%CI 51%-96.0%). In two proof-of-concept studies designed by the same group, heart rate and blood pressure decreased in 37 patients [44], while respiratory rate and discomfort decreased in 33 patients [45].…”
Section: Table 2 (Continued)supporting
confidence: 90%
“…The present study is the rst randomized study about VR evaluating the improvement of baseline patient's overall comfort in a mixed medical-surgical ICU, compared to music-therapy and standardrelaxation. A recent review on VR in ICU reported 21 studies, mostly of them being observational, noncomparative, feasibility studies [42], whose reports are consistent with the present study with a completion rate of 74%, (95%CI: 51%-96.0%). In two proof-of-concept studies designed by the same group, heart-rate and blood-pressure decreased in 37 patients [43], while respiratory rate and discomfort decreased in 33 patients [44].…”
Section: Discussionsupporting
confidence: 90%
“…Web‐based interventions, such as video conferencing and text messages, have been alternatives to providing interhuman contact, information and support 55,56 . Virtual reality could have great potential in the clinical ICU environment 33,57 . E‐health applications, such as integrated health apps and home self‐monitoring, might be beneficial for individuals who can proactively check their health by means of regularly completed short digital questionnaires recording expected symptoms, thus raising awareness or reducing deterioration through timely professional support.…”
Section: Discussionmentioning
confidence: 99%